Radiographic Assessment of the Marginal Bone Loss Around the Implant Before and After the Prosthesis Placement—A Comparative Study - Mohammad Jalaluddin; Aradhana Rathod; Shilpa Mailankote; Liya Neha Bipinchandra; BS Harsha Raj; Anupama Ahirwar (Journal of Pharmacy and Bioallied Sciences)
Aim: The present investigation performed the CBCT to measure the marginal bone loss surrounding the implant both before and after the prosthesis was placed. Materials and Methods: Within the age range of 21 to 45 years, a total of 20 patients were involved, and all participants gave their informed consent. Immediate implant was inserted and ceramic prosthesis was prepared and given to the patients. Radiographic assessment was carried out using the CBCT at baseline, three months, and six months following the prosthesis. The circumference of the crestal bone level around the implant was measured in all directions (mesial, distal, buccal, and palatal), using the implant’s first thread as a standard reference point. Results: The change of the mean marginal bone level at the time of implant placement to three months after the prosthesis was at mesial 1.32 ± 0.02 to 1.46 ± 0.10, at distal 1.46 ± 0.08 to 1.94 ± 0.14, at buccal 1.28 ± 0.01 to 1.40 ± 0.06, at palatal 1.20 ± 0.03 to 1.22 ± 0.04. The change of the mean marginal bone level at the time of implant placement to six months after the prosthesis was at mesial 1.32 ± 0.02 to 1.84 ± 0.12, at distal 1.46 ± 0.08 to 2.38 ± 0.02, at buccal 1.28 ± 0.01 to 1.78 ± 0.04, at palatal 1.20 ± 0.03 to 1.34 ± 0.01. Conclusion: The current investigation came to the conclusion that the CBCT provides all the diagnostic information required for an implant to be placed successfully.